The Role of Epstein-Barr Virus in the Pathogenesis of Autoimmune Diseases - Natalia Morawiec; Bożena Adamczyk; Aleksandra Spyra; Mikołaj Herba; Sylwia Boczek; Natalia Korbel; Piotr Polechoński; Monika Adamczyk-Sowa (Medicina)
Background and Objectives: The Epstein-Barr virus (EBV) belongs to the gamma herpesviruses family. Evidence from the literature suggests that EBV initiates immune responses and the production of antibodies. Chronic or recurrent EBV infections may be associated with autoimmune diseases such as systemic lupus erythematosus, Sjögren’s syndrome, rheumatoid arthritis, multiple sclerosis, or inflammatory bowel diseases. This review aims to establish the role of EBV in the development and progression of autoimmune diseases. Materials and Methods: A literature search was conducted using PubMed, PMC, Google Scholar, and SCOPUS. Relevant studies, including meta-analyses, case-control studies, literature reviews, cross-sectional studies, and longitudinal studies, were identified through titles and abstracts screening for a comprehensive analysis. Results: Our study revealed a strong association between EBV infection and several autoimmune diseases, including multiple sclerosis, systemic lupus erythematosus, rheumatoid arthritis, and inflammatory bowel disease. Epstein-Barr virus seropositivity was significantly higher in affected individuals. Elevated EBV-specific antibodies correlated with disease onset and severity. EBV DNA and latency proteins were detected in diseased tissues, alongside immune dysregulation and molecular mimicry mechanisms. Conclusions: Our findings highlight that EBV may be an important factor in autoimmune disease pathogenesis, contributing to immune activation and tissue damage. Further research is needed to explore EBV-targeted therapies and their potential in preventing or managing autoimmune diseases.